Penambahan Ekstrak Etanol Buah Naga Merah (Hylocereus polyrhizus) Afkir pada Pembuatan Sabun Cair Berbasis Virgin Coconut Oil - Windi Windi; Ni Ketut Sumarni; Jaya Hardi (Jurnal Ilmiah Teknik Kimia, 2022)
Rejected Dragon fruit (Hylocereus polyrhizus) is rich in anthocyanin compounds that can be used as additional ingredients in liquid soap formulas, thereby increasing the quality of soap as an antioxidant that protects the skin from the effects of sunlight and pollution. The purpose of this research was to determine the mass of rejected dragon fruit extract which produced liquid soap with the highest pH and foam stability and the best viscosity value. The research design used was a completely randomized design (CRD) with a factorial pattern with the independent variable being the concentration of rejected dragon fruit extract with four treatment levels of 0, 1.5, 3, and 4.5 grams of extract per 250 grams of soap formula and storage time consisting of four levels of 0, 7, 14, and 21 days. The best liquid soap formula was obtained when using a rejected dragon fruit extract concentration of 1.5 grams per 250 grams of soap formula (SW1 formula) with a foam stability value of more than 90% until 21 days of storage. Formula SW1 also has a stable pH during storage, which is in the pH range of 7 – 9. The viscosity value of the SW1 formula reaches 13.25 N/m2 with a free alkali value of 2.48%. The SW1 formula with a rejected dragon fruit extract content of 1.5 grams per 250 grams of soap formula can be developed as a new formula for the manufacture of liquid soap which is rich in antioxidant compounds.